Nasopharyngeal carriage of penicillin-resistant Streptococcus pneumoniae in healthy children - (:unkn) unknown (TURKISH J PEDIATRICS, 2007)
Streptococcus pneumoniae carriage is a risk factor for the development of respiratory system infections and the spread of penicillin-resistant strains. The aim of this study was to investigate nasopharyngeal carriage of S. pneumoniae in healthy children and resistance to penicillin and other antimicrobials and to assess related risk factors. Nasopharyngeal specimens collected from healthy children less than six years of age, visiting a Mother and Child Health Center for health control, were investigated microbiologically between February-March 2004. Carriage rate was 37.2% (n=112/301); 33.9% intermediate and 5.4% high penicillin resistance were detected. According to multivariate analysis, carriage rate was inversely related to number of rooms (OR:0.574) and child age (OR:0.978), while penicillin resistance was correlated well with antibiotic use in the last two months (OR:2.193). Decreased sensitivity plus resistance to other antimicrobials were: trimethoprim-sulfamethoxazole (TMP-SMX) 45.6%; erythromycin 16.1 %, tetracycline 16.1 %; clindamycin 9.8%, and ofloxacin 3.6% in pneumococcal isolates, which increased significantly (p<0.05) to 72.7%, 31.8%, 27.3%, 20.5%, and 6.8%, respectively, in penicillin non-sensitive S. pneumoniae (PNSSP) except for ofloxacin. Overall multidrug resistance was 17.9%, while PNSSP exhibited a resistance rate of 38.6%. In conclusion, S. pneumoniae carriage rates determined in healthy children were high and PNSSP strains also showed increased resistance to other antimicrobials.
Keywords: S. pneumoniae; carriage; penicillin resistance; ANTIMICROBIAL RESISTANCE; RISK-FACTORS; EPIDEMIOLOGY; MULTICENTER; PNEUMOCOCCI; PATHOGENS; INFANTS